Scalable and Transfer-Free Fabrication of MoS2/SiO2 Hybrid Nanophotonic Cavity Arrays with Quality Factors Exceeding 4000 - Sebastian Hammer (Nature Portfolio, 2017)
Abstract We report the fully-scalable fabrication of a large array of hybrid molybdenum disulfide (MoS2) - silicon dioxide (SiO2) one-dimensional, free-standing photonic-crystal cavities capable of enhancement of the MoS2 photoluminescence at the narrow cavity resonance. We demonstrate continuous tunability of the cavity resonance wavelength across the entire emission band of MoS2 simply by variation of the photonic crystal periodicity. Device fabrication started by substrate-scale growth of MoS2 using chemical vapor deposition (CVD) on non-birefringent thermal oxide on a silicon wafer; it was followed by lithographic fabrication of a photonic crystal nanocavity array on the same substrate at more than 50% yield of functional devices. Our cavities exhibit three dominant modes with measured linewidths less than 0.2 nm, corresponding to quality factors exceeding 4000. All experimental findings are found to be in excellent agreement with finite difference time domain (FDTD) simulations. CVD MoS2 provides scalable access to a direct band gap, inorganic, stable and efficient emitter material for on-chip photonics without the need for epitaxy and is at CMOS compatible processing parameters even for back-end-of-line integration; our findings suggest feasibility of cavity based line-narrowing in MoS2-based on-chip devices as it is required for instance for frequency-multiplexed operation in on-chip optical communication and sensing.